Traditional Knowledge and Modern Green Technologies: Pathways for SME Sustainability in Kathmandu, Nepal (International Journal of Atharva, 2025)
Background: Nepal's rapid socio-economic transformation intersects with its rich cultural heritage, where traditional business practices, rooted in community values and social networks, form the backbone of its SME sector. Understanding the interaction between these indigenous cultural practices and the emerging principles of the green economy is crucial for sustainable development.Objectives: This study aimed to (1) assess cultural business practices and perceptions of the green economy within Nepalese SMEs, and (2) examine the relationship between these cultural practices and green economic principles.Methods: A quantitative, descriptive-correlational research design was employed. Data were collected via a structured questionnaire from 219 owners and managers of SMEs in the Kathmandu Metropolitan area, especially among Newars. Analysis utilized descriptive statistics and Kendall’s tau-b correlation.Findings: Respondents expressed neutral perceptions (Mean=2.99) on whether traditional business practices are inherently sustainable. However, cultural values like community sharing and frugality were seen to support green principles (Mean=3.21). A significant concern was that modern trends are erasing traditional eco-friendly practices (51.6% agreed). There was strong optimism that cultural industries can drive the green economy (58% agreed) and that blending traditional knowledge with modern technology can boost the economy (66.7% agreed). A major challenge identified was accessing green financing (52.1% agreed). Critically, a statistically significant, moderate positive correlation was found between cultural business practices and the green economy (τ_b = .450, p < .01).Conclusion: The findings indicate that Nepal's traditional cultural business practices and values are perceived to be aligned with and supportive of green economic principles. Cultural industries are seen as a potential driver for a sustainable economy.Implication: Policymakers and business development agencies should leverage compatible cultural values to promote green economy initiatives. Strategies should focus on integrating traditional knowledge with modern technology and, crucially, addressing the barriers to green financing and certifications for SMEs.